2010
DOI: 10.3201/eid1605.091314
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiae in Gulf Coast Ticks,Arkansas, USA

Abstract: To determine the cause of spotted fever cases in the southern United States, we screened Gulf Coast ticks (Amblyomma maculatum) collected in Arkansas for rickettsiae. Of the screened ticks, 30% had PCR amplicons consistent with Rickettsia parkeri or Candidatus Rickettsia amblyommii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Serologic cross-reactivity is well documented among Rickettsia spp. (Breitschwerdt et al 1987, Apperson et al 2008, Paddock et al 2008, Paddock et al 2010, Trout et al 2010. In experimental infections with mice and dogs, the highest titer is generated against the specific Rickettsia sp.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Serologic cross-reactivity is well documented among Rickettsia spp. (Breitschwerdt et al 1987, Apperson et al 2008, Paddock et al 2008, Paddock et al 2010, Trout et al 2010. In experimental infections with mice and dogs, the highest titer is generated against the specific Rickettsia sp.…”
Section: Discussionmentioning
confidence: 96%
“…amblyommii,'' R. montanensis, R. parkeri, or other Rickettsia spp. that have not yet been described (Apperson et al 2008, Paddock et al 2008, Paddock et al 2010, Trout et al 2010, McQuiston et al 2012. A previous survey of naturally infected dogs for antibodies to Rickettsia spp.…”
Section: Introductionmentioning
confidence: 93%
“…In the United States the historic range of A. maculatum was reported to be within 160 km (100 miles) of the Gulf Coast and coastal southern Atlantic States from South Carolina to Texas (Bishopp and Trembley 1945). However, inland populations of the tick have been recognized in Oklahoma and Kansas since the 1970s (Semtner andHair 1973, Teel et al 2010), and more recently in Arkansas (Trout et al 2010). Additionally, incidental collections of A. maculatum throughout the later half of the 20th century, thought to have been due to migratory bird drop-offs (Scott et al 2001), have been reported from Iowa to Maine (Teel et al 2010), including Virginia (Sonenshine et al 1965), where historically four to five specimens are collected annually in Fairfax County (unpublished data), but it has only been within the last decade that the tick has been recognized as a vector of public health importance.…”
Section: Introductionmentioning
confidence: 91%
“…R. parkeri has been found infecting A. maculatum throughout much of its range. Positive specimens have been detected from at least nine states: Alabama, Arkansas, Florida, Georgia, Kentucky, Mississippi, Oklahoma, South Carolina, and Texas (Parker et al 1939, Philip and White 1955, Philip et al 1978, Sumner et al 2007, Edwards et al 2011, Paddock et al 2010, Trout et al 2010). Here we report high rates of R. parkeri infection in Gulf Coast ticks collected from Fairfax County, Virginia.…”
Section: Introductionmentioning
confidence: 93%
“…The first confirmed human infection with R. parkeri was reported in 2004, and approximately 15 cases of R. parkeri rickettsiosis have been described in the literature since that initial report (66)(67)(68)(69)(70). In the United States, Amblyomma maculatum (the Gulf Coast tick) is the principal vector for these bacteria, and R. parkeri is detected in 8% to 43% of questing adult A. maculatum ticks collected in states along the Gulf Coast and the southern Atlantic region (95)(96)(97)(98)(99)(100)(101). R. parkeri is distributed throughout multiple tissues of infected A. maculatum ticks, including the salivary glands, the midgut, the Malpighian tubules, and the ovaries (102).…”
Section: North and Central Americamentioning
confidence: 99%